ENGINEERED CHO DG-44 DPO CELL METABOLISM TO ENHANCE SIALYLATION OF RECOMBINANT PROTEIN DARBEPOETIN (DPO) - Amalia Limeilati, Nur
Erythropoietin alpha is a protein therapeutic product for anaemia caused by chronic kidney disease or cancer chemotherapy. One of erythropoietin alpha derivative is darbepoetin alpha (DPO). DPO developed by PT Bio Farma was characterized by Batavia Biosciences, Netherland. Control molecule is DPO originator, Aranesp®. The result showed a lighter molecular weight, more basic isoforms instead of acidic and only half the sialic acid content than those of originator, Aranesp®. These characteristics influence its biological activity and in vivo half-life, making the effort to increase the sialic acid content of the DPO molecule is paramount. This study aims to increase sialic acid content in DPO isoforms. A series of experiments were held which include comparing and shifting the culture temperature between 37°C and 32.5°C, pH ranging between 6.8-7.4, glucose ranging at 25-50 mM, adding N-acetyl-D-mannosamine as the sialic acid precursor and galactose as the terminal binding site for sialic acid. The culture at 37°C grown for 14 days while the culture with temperature shifting to 32.5°C grown for 18 days. Both culture harvested when the viability reaches 80% to prevent protease and glycosidase affecting the DPO. To see the effect those parameters in DPO molecule, IEF and sialic acid assay were used. Viable cell density, cell viability percentage, pH, glucose, lactate and ammonia were measured every day as part of in-process control (IPC), with DPO titer added to see the effect of the experiment on sialic acid content. From the IPC data, glucose consumption was equivalent to the lactate produced, so was the glutamine consumption to the ammonia produced by the cell. Using the EX-CELL Feed at glucose range 2 - 4.5 g/L and pH range 7-7.2 while adding 20 mM N-Acetyl-D-mannosamine and 0.6% galactose periodically increase the sialic acid content in DPO molecule which was shown in the IEF result where the isoforms bands were more acidic and parallel with the originator. Shifting the temperature to 32.50C increased the DPO titre up to 1.58 times than 370C. From this study it was concluded that DPO sialic acid content can be increased to reach the originator level using temperature shifting from 370C to 32.50C, pH range 7 – 7.2 and feed combination EX-CELL feed, 20 mM N-acetyl-D-mannosamine and 0.6% galactose.